(untitled) (Computer systems and information technologies, 2022)
The healthcare sector in Ukraine has long been in need of change, and the many opportunities of blockchain technology can help it lead the transformation of this sector and ensure compliance with the requirements of efficiency, safety, novelty and economic benefits. Blockchain will transform medical enterprises and improve the quality of service, allowing new ecosystems and new business models to develop. Healthcare information stored in the blockchain can change the way clinical information is stored, as well as how information is shared in the organization, with healthcare partners, payers and, most importantly, patients. Blockchain decentralizes medical information by increasing the availability, efficiency, transparency, and credibility of data, but also requires careful planning to maximize the benefits it brings. With the help of the blockchain, users can store important medical data, the authenticity of which can be verified if there is a suspicion of forgery. In addition, cryptographic algorithms can be used to ensure the confidentiality of medical data (for example, an attacker will not be able to read the text if he stole data). Thus, the current challenge is the need to manage medical data based on blockchain technologies. The reputation of the medical institution (as a blockchain miner) is an important indicator, as the blocks are recorded by verified pre-selected validators and are in fact moderators of the system. It is to determine such validators that the value is not the number of tokens, but reputation, ie the blockchain according to a certain algorithm, taking into account the reputation, chooses a validator who will write the next block. Reputation grows with active life in the blockchain ecosystem and interaction with other participants. The better the reputation - the greater the chance of creating the next block. Therefore, the method of assessing the reputation of a medical institution (as a miner of blockchain), which allows to calculate and assess the reputation of a medical institution, was further developed in the article. Experiments on blockchain-based medical data management using the developed method of assessing the reputation of a medical institution (as a blockchain miner) - experiments to assess the reputation of a medical institution (for example, two different family medicine clinics) - as a blockchain miner.